Development of Kobela Media in Class IV Elementary School Fraction Material - Wulandari, Fitria; Sari, Arissona Dia Indah; Umam, Nanang Khoirul (JMEA : Journal of Mathematics Education and Application, 2025)
This study aims to develop learning media for learning boxes (Kobela) to improve understanding of fraction material with denominator eight for fourth grade students at UPT SDN 98 Gresik. The background of this study is the lack of learning media that supports the delivery of fraction material, so that learning relies more on reading books. This study uses a research and development method with the ADDIE approach which includes five stages: analysis, design, development, implementation, and evaluation. Data collection techniques include questionnaires, ability tests, media and material validation, and interviews. The results of the study showed that the Kobela media has a very high level of validity with an average validation value of 97% from media experts and material experts. In addition, the results of the student ability test showed an N-gain value of 1.6, which is included in the high category. Based on these results, the Kobela media was declared very feasible and effective in improving students' understanding of fraction material.